2011
DOI: 10.1002/ijc.26034
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of sunitinib against skeletal metastatic renal cell carcinoma through inhibition of osteoclast function

Abstract: We investigated the inhibitory effect of sunitinib, a newly approved multitargeted tyrosine kinase inhibitor, against the progression of renal cell cancer (RCC) bone metastases in vivo. In vitro cell proliferation was determined using the MTS assay. To investigate the inhibitory effects of sunitinib in vivo, we established luciferase-labeled ACHN Luc cells derived from papillary RCC. Mice in which ACHN Luc cells had been transplanted into the left ventricle to establish bone metastases were treated orally with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
(64 reference statements)
1
21
0
Order By: Relevance
“…The antitumor activity of sunitinib has been shown in preclinical and clinical studies (7,18). Tumor regression has been shown in different xenograft models of colon cancer, breast cancer, non-small cell lung cancer, melanoma, glioblastoma and renal carcinoma (18,(29)(30)(31)(32)(33). Sunitinib clearly inhibited cell proliferation in vitro and tumor growth in vivo in the present study (Figs.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The antitumor activity of sunitinib has been shown in preclinical and clinical studies (7,18). Tumor regression has been shown in different xenograft models of colon cancer, breast cancer, non-small cell lung cancer, melanoma, glioblastoma and renal carcinoma (18,(29)(30)(31)(32)(33). Sunitinib clearly inhibited cell proliferation in vitro and tumor growth in vivo in the present study (Figs.…”
Section: Discussionsupporting
confidence: 62%
“…Sunitinib is an oral inhibitor with antiangiogenic and antitumor activities and inhibits multiple receptor tyrosine kinases, including VEGF receptors, PDGF receptors and c-KIT, which are involved in angiogenesis (7). The antitumor activity of sunitinib has been shown in preclinical and clinical studies (7,18). Tumor regression has been shown in different xenograft models of colon cancer, breast cancer, non-small cell lung cancer, melanoma, glioblastoma and renal carcinoma (18,(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5.3c) of sunitinib with the native ligand shows dotted lines representing H-bonds with the target protein. Further, very recent reports presented the use of sunitinib for renal cell carcinoma bone metastases [27], an activity related to bone resorption. This likeliness of the data made us search further for similarity in the acquired results and experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…Maita et al demonstrated that sunitinib prevented the growth of RCC cells in a bone metastatic mouse model and caused significant declines in bone turnover markers in patients treated with sunitinib. (9) Additionally, the lower rate of SREs could reflect an underestimation of actual events given that the database was not designed to capture SREs and adverse event monitoring occurred only during the period for which patients were on the clinical trial. We did not observe a correlation between SRE rate and survival.…”
Section: Discussionmentioning
confidence: 99%